A pharmacogenetic study implicates NINJ2 in the response to Interferon-β in multiple sclerosis. (August 2020) - Peroni, Silvia; Sorosina, Melissa; Malhotra, Sunny; Clarelli, Ferdinando; Osiceanu, Ana Maria; Ferrè, Laura; Roostaei, Tina; Rio, Jordi; Midaglia, Luciana; Villar, Luisa María; Álvarez-Cermeño, José Carlos; Guaschino, Clara; et al.
Background: Multiple sclerosis (MS) is a disease in which biomarker identification is fundamental to predict response to treatments and to deliver the optimal drug to patients. We previously found an association between rs7298096, a polymorphism upstream to the NINJ2 gene, and the 4-year response to interferon-β (IFNβ) treatment in MS patients. Objectives: To analyse the association between rs7298096 and time to first relapse (TTFR) during IFNβ therapy in MS patients and to better investigate its functional role. Methods: Survival analysis was applied in three MS cohorts from different countries ( n  = 1004). We also studied the role of the polymorphism on gene expression using GTEx portal and a luciferase assay. We interrogated GEO datasets to explore the relationship between NINJ2 expression, IFNβ and TTFR. Results: Rs7298096AA patients show a shorter TTFR than rs7298096G -carriers (Pmeta-analysis  = 3 × 10 −4, hazard ratio = 1.41). Moreover, rs7298096AA is associated with a higher NINJ2 expression in blood ( p  = 7.0 × 10 −6 ), which was confirmed in vitro ( p  = 0.009). Finally, NINJ2 expression is downregulated by IFNβ treatment and related to TTFR. Conclusions: Rs7298096 could influence MS disease activity during IFNβ treatment by modulating NINJ2 expression in blood. The gene encodes for an adhesion molecule involved in inflammation and endothelial cells activation, supporting its role in MS.